Phosphorus sorption characteristics in the Sahel: Estimates from soils in Mali - Kouyate Aliou Badara; Logah Vincent; Abaidoo R. C; Tetteh Francis Marthy; Bonsu Mensah; Dembélé Sidiki Gabriel (Aimpress, 2023)
This article is published by Aimpress,2023 and is also available at DOI: 10.3934/agrfood.2023053